(untitled) (World Economics and Finance Bulletin, 2023)
The paper discusses the distinctions between Islamic banking goods and services and standard banking services, as well as the key reasons for the benefits and growing popularity. The first steps toward the establishment of the Islamic financial services market in Uzbekistan are also discussed